Effects of Citrus Flavonoids Against Microvascular Damage Induced by Hypoperfusion and Reperfusion in Rat Pial Circulation. (July 2015) - Mastantuono, Teresa; Battiloro, Laura; Sabatino, Lina; Chiurazzi, Martina; Di Maro, Martina; Muscariello, Espedita; Colantuoni, Antonio; Lapi, Dominga
Abstract Objective The aim of the present study was to investigate the in vivo protective effects of hesperidin or diosmin or apigenin on damage induced by transient BCCAO and reperfusion. Methods Rat pial microcirculation was observed through a closed cranial window, using fluorescence microscopy. Pial arterioles were classified in five orders according to the Strahler's method. Results After 30 BCCAO and 60 minutes reperfusion, rats showed decreased arteriolar diameter, microvascular leakage, leukocyte adhesion, and reduction in capillary perfusion. Hesperidin and diosmin abolished the reduction in arteriolar diameter, while higher dose apigenin induced dilation by 21.7 ± 2.0% in order three arterioles RE. Nitric oxide synthase inhibition attenuated significantly hesperidin or diosmin or apigenin's effects on arteriolar diameter. Moreover, all these substances reduced microvascular leakage as well as leukocyte adhesion in dose‐related manner, while capillary perfusion was protected. Furthermore, reduction in infarcted area and decrease in ROS production were observed. Conclusions Hesperidin, diosmin, and apigenin showed dose‐related protective effects on hypoperfusion–reperfusion injury, causing nitric oxide release and attenuating tissue edema and leukocyte adhesion.